Biomass and Remote Sensing of Biomass - Atazadeh, Islam (IntechOpen, 2011)
Generally, the term biomass is used for all materials originating from photosynthesis. However, biomass can equally apply to animals. Conservation and management of biomass is very important. There are various ways and methods for biomass evaluation. One of these methods is remote sensing. Remote sensing provides information about biomass, but also about biodiversity and environmental factors estimation over a wide area. The great potential of remote sensing has received considerable attention over the last few decades in many different areas in biological sciences including nutrient status assessment, weed abundance, deforestation, glacial features in Arctic and Antarctic regions, depth sounding of coastal and ocean depths, and density mapping. The salient features of the book include: Several aspects of biomass study and survey; Use of remote sensing for evaluation of biomass; Evaluation of carbon storage in ecosystems; Evaluation of primary productivity through case studies